Cognition Recovery Method Sebagai Pendekatan Hermeneutika Berbasis Lontar Dalam Meluruskan Miskonsepsi Yajña - Anak Agung Gde Oka Widana; Anak Agung Istri Dalem Hana Yundari; Ni Komang Sukra Andini; Desak Nyoman Diah Setyawati Anom (Jurnal Penelitian Agama Hindu, 2026)
The practice of yajña in the era of technological dominance has entered a critical period due to the rise of the phenomenon of the Religion Misconception Pandemic which causes yajña practitioners to fail to understand the meaning and only focus on quantity. Therefore, the Cognition Recovery Method is important to be realized through a renewable innovative method based on literature to create an innovative and relevant method in overcoming the Religion Misconception Pandemic when performing yajña. The data analysis techniques are (1) analyzing the referred lontar, (2) tracing the Religion Misperception Pandemic regarding the hermeneutics of yajña in the referred lontar, (3) developing a Cognition Recovery Method to correct yajña misconceptions, and (4) presenting the findings in a structured manner. The results of the study indicate that the lontar-based Cognition Recovery Method is quite effective in correcting yajña misconceptions through efforts; (1) Cognition Recovery Method Pro Kayika, in the form of introducing ritual sanctions, curative efforts, and behavioral control, (2) Cognition Recovery Method Pro Wacika, in the form of controlling aspects of speech and ritual sanctions, and (3) Cognition Recovery Method Pro Manacika, in the form of controlling thoughts. These efforts contribute to enriching the number of renewable methods and can be used in science by including meaningful analysis based on literary studies as a legacy of local wisdom. These efforts play a role in understanding in depth what, how, and why yajña is obligatory for Hindus to carry out.